Mini channel heat exchanger - Đặng Thành Trung; Não Minh Daly (Journal of Technical Education Science, 2013)
The study was presented to design and manufacture a minichannel heat exchanger using UV light technology to bond between aluminum and PMMA (polymethyl methacrylate) plates together. The minichannel heat exchanger size is only 64% the size of the scooter radiator which made from manufacturer; however, the heat transfer rate obtained from the minichannel heat exchanger is higher than or equal to that obtained from the radiator, particularly when air velocity is from 1.2 m/s to 3.5 m/s and the mass flow rate of the fluid varies from 2.46g/s to 4.1g/s. In addition, when the minichannel heat exchanger is used, it will take advantage of the forced convection by scooter moving, so the scooter will not need the fan as it is using.